Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2466477
|View full text |Cite
|
Sign up to set email alerts
|

Social media and the police

Abstract: With this paper we take a first step to understand the appropriation of social media by the police. For this purpose we analyzed the Twitter communication by the London Metropolitan Police (MET) and the Greater Manchester Police (GMP) during the riots in August 2011. The systematic comparison of tweets demonstrates that the two forces developed very different practices for using Twitter. While MET followed an instrumental approach in their communication, in which the police aimed to remain in a controlled posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 14 publications
2
60
0
5
Order By: Relevance
“…The State, of course, has the authority to seek this information, and smartphone logs, GPS locations, text messages, Internet search history, or social media posts are all part of this remit. Moreover, a growing body of work has considered how police forces and police officers use social media (Davis, Alves, and Sklansky 2014; Denef, Bayerl and Kaptein 2013; Trottier and Fuchs 2014). Alternatively, government have sought to target and decrypt WhatsApp conversations in order to prevent terror attacks (Guardian 2017).…”
Section: Social Media Codementioning
confidence: 99%
“…The State, of course, has the authority to seek this information, and smartphone logs, GPS locations, text messages, Internet search history, or social media posts are all part of this remit. Moreover, a growing body of work has considered how police forces and police officers use social media (Davis, Alves, and Sklansky 2014; Denef, Bayerl and Kaptein 2013; Trottier and Fuchs 2014). Alternatively, government have sought to target and decrypt WhatsApp conversations in order to prevent terror attacks (Guardian 2017).…”
Section: Social Media Codementioning
confidence: 99%
“…For example, several research groups have demonstrated that emergency managers and responders understand the value of social media for crisis communication (Hughes & Palen, 2012). In addition, there have been several studies of emergency managers and responders who have used social media to get the word out during a crisis (Denef et al, 2013;Hughes et al, 2014;Denis et al, 2014;Sutton et al, 2012). More directly, there have been several research efforts to understand how emergency managers and responders have tried to influence the public's information or behavior via social media during crises (Hughes & Chauhan, 2015;Sutton et al, 2014).…”
Section: The Use Of Microblogged Data In Disaster Responsementioning
confidence: 99%
“…Unsurprisingly, this is closely associated with the data-sharing policies of different venues. Multidisciplinary journals such as Nature and Science mandate authors to include data such that reviewers and other researchers can replicate results 8 and accordingly are a notable exception to this trend, with 40% of papers sharing their data. We are not aware of any conferences in our survey which mandate data necessary for replication must be shared, although conferences such as SOUPS do allow authors to include appendices which support replication.…”
Section: Few Osn Researchers Share Their Datamentioning
confidence: 99%
“…These providers assert control over how the data that they host are used, and actively disallow large datasets of their content to be published. 12 This may impede one of the tenets of reproducible research, particularly when work concerns a specific corpus of content, such as Denef et al's examination of tweets during the 2011 London riots [8], rather than a random sample of content generated by a certain population. If OSN data cannot be directly shared, then it might be possible to instead repeat the experiment, but only if the sampling strategy of the original experiment can be replicated.…”
Section: Introductionmentioning
confidence: 99%